Facile preparation of carbon sphere supported molybdenum compounds (P, C and S) as hydrogen evolution electrocatalysts in acid and alkaline electrolytes. (February 2017) - Wu, Zexing; Wang, Jie; Liu, Rong; Xia, Kedong; Xuan, Cuijuan; Guo, Junpo; Lei, Wen; Wang, Deli
Abstract: Efficient electrocatalysts for hydrogen evolution reaction (HER) were developed based on the homogeneous dispersion of molybdenum composites (MoP, Mo2 C, MoS2 ) on a glucose- derived carbon sphere matrix obtained by simply changing the precursors during the high temperature treatment. The potential composite materials showed different performance characteristics in different experimental designs. The as-synthesized MoP showed the best HER performance in acid medium with a low overpotential of 136 mV obtained at 10 mA cm −2, while Mo2 C-C showed the lowest overpotential for HER in alkaline medium, and for MoS2 -C, which exhibited few layers structure (less than three layers), exhibiting favorable catalytic performance in both acid and alkaline electrolytes. Both MoP-C and Mo2 C-C showed negligible overpotential loss after 5000 cycles in acid medium, but were relative unstable in alkaline medium. Moreover, the carbon sphere matrix improved the catalytic performance of molybdenum compounds by alleviating the aggregation of catalysts, providing sufficient area for electrolyte contact, and facilitating electron transfer. This work demonstrates a facile avenue to prepare cost-effective molybdenum compounds for HER. Furthermore, electrochemical performance of the catalysts was investigated in both acid and basic media. Graphical abstract: A novel and facile synthetic route was developed for the controllable preparation of molybdenum compounds (MoP, Mo2 C and MoS2 ) supported on carbon spheres by post high temperature treatment of the solvothermal products. The catalytic activities for hydrogen evolution reaction (HER) of Molybdenum compounds were investigated in both acid and basic media systemically. Highlights: A facile way is developed to synthesize various molybdenum compounds. Electrocatalytic performance of the catalysts is investigated detailed in both acid and alkaline media. The prepared catalysts possess different structures, including few layered and nanoparticle morphologies. Carbon sphere plays an important role on improving the catalytic activity.